Monitoring of land use intensification and linkage to soil erosion in Nigeria and Benin - Junge, B.; Abaidoo, Robert C.; Chikoye, David; Alabi, T.R.; Stahr, Karl (2006)
The growing population and the increasing food demand in sub-Saharan Africa require comprehensive land use intensification. Land scarcity and soil degradation are some consequences that necessitate enhanced land use management by using remote sensing data. This study presents the analyses of aerial photographs and satellite images for inventory land use and its changes within time as well as for monitoring soil erosion. The example from a pilot village located in southern Benin shows the increase of the cropping area and the growth of erosion gullies within the last decades. As the data provide the basis for installing soil conservation techniques, they are a useful tool to restore soil productivity and to cope with the food demand in the country.